Suicide prevention in the world's armies (review of suicide factors) - Syropjatov, Олег; Dzeruzhynska, Наталія; Korshevnyuk, Dmytro (Psychosomatic Medicine and General Practice, 2021)
This is a conference abstract from the ІV Scientific and Practical Conference "Psychosomatic medicine: science and practice". It is dedicated to the suicide prevention in the world's armies. The suicidal behavior of military personnel is a complex process, for which it is necessary to consider the personality of a serviceman from different angles (anamnesis of the family and the serviceman himself, personality traits revealed during psychological study, observation of the behavior of a serviceman during military service) and take into account all possible risk factors for the development of suicidal behavior, there is a possibility of preventing suicide.